Antibacterial Activity of Hen Egg White Lysozyme Denatured by Thermal and Chemical Treatments - Rubén Vilcacundo; Pilar Méndez; Walter Reyes; Herman Romero; Adelita Pinto; Wilman Carrillo (MDPI AG, 2018)
The aim of this study was to increase the antibacterial spectrum of modified hen egg white lysozyme (HEWL) with thermal and chemical treatments against Gram-negative bacteria. The antibacterial activity of heat-denatured HEWL and chemical denatured HEWL against Gram-negative and Gram-positive bacteria was evaluated in 15 h of incubation tests. HEWL was denatured by heating at pH 6.0 and pH 7.0 and chemical denaturing was carried out for 1.0, 1.5, 2.0, and 4.0 h with DL-Dithiothreitol (DTT). HEWL modified by thermal and chemical treatments was characterized using the sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) electrophoresis method. Heat-denatured HEWL lytic activity against Micrococcus lysodeikticus lessened with increasing temperature and time of incubation with the chemical agent (DTT). The loss of lytic activity in modified HEWL suggests that the mechanism of action of the antibacterial activity is not dependent on the lytic activity. Thermal and chemical treatments of HEWL enabled the production of oligoforms and increased antibacterial activity over a wider spectrum. Heat-denatured HEWL at pH 6.0 and chemically-denatured HEWL increased the HEWL antibacterial spectrum against Gram-negative bacteria (Escherichia coli ATCC 25922). HEWL at 120 °C and pH 6.0 (1.0 mg/mL) inhibited 78.20% of the growth of E. coli. HEWL/DTT treatment for 4.0 h (1.0 mg/mL) inhibited 68.75% of the growth E. coli. Heat-denatured HEWL at pH 6.0 and pH 7.0 and chemically-denatured HEWL (1.0, 1.5, 2.0, and 4.0 h with DTT) were active against Gram-positive bacteria (Staphylococcus carnosus CECT 4491T). Heat-denatured and chemical-denatured HEWL caused the death of the bacteria with the destruction of the cell wall. LIVE/DEAD assays of fluorescent dye stain of the membrane cell showed membrane perturbation of bacteria after incubation with modified HEWL. The cell wall destruction was viewed using electron microscopy. The results obtained in this study suggest that heat-denatured HEWL at pH 6.0 and chemical-denatured HEWL treatments increase the HEWL antibacterial activity against Gram-negative bacteria.